A Bis(Aquated) Mn(II)-Based MRI Contrast Agent with a Rigid Hydroquinazoline Unit: Synthesis, Characterization, and in Vivo MR Imaging Study - Mallik, Riya; Saha, Muktashree; Sarmah, Amrit; Singh, Vandna; Mohan, Hari; Bhat, Priyanka; Kumaran, S. Senthil; Mukherjee, Chandan (ACS applied bio materials, 2024)
Since the finding of nephrogenic systemic fibrosis (NFS) in patients with renal impairment and the long-term accumulation of Gd(III) ions in the central nervous system, the search for nongadolinium ion-based MRI contrast agents made of nutrient metal ions has drawn paramount attention. In this context, the development of Mn(II)-based MRI contrast agents has been a subject of interest for the last few decades. Herein, we report a pentadentate ligand (Li2[BenzPic2]) composed of two picolinate moieties and a rigid 1,2,3,4-tetrahydroquinazoline unit and the corresponding bis(aquated) Mn(II) complex (Complex 1). The complex exhibited high thermodynamic stability (log K cond = 11.62) and kinetic inertness similar to that of the clinically approved Gd(III)-based contrast agent Magnevist. Complex 1 exerted longitudinal relaxivity (r 1) of 5.32 mM–1 s–1 at 1.41 T, 37 °C, pH 7.4, and it increased by 3.6-fold in the presence of serum albumin protein, confirming a substantial rigidifying interaction (albumin association constant K A = 1.66 × 103 M–1) between the protein and the amphiphilic (log P = −0.45) contrast agent. An intravenous dose of 0.08 mmol/kg in a healthy mouse, excellent MRI signal intensity enhancement in the vasculature of the mouse liver, and brightened images of the gallbladder, kidney, and liver were realized.